PENERAPAN REBUSAN DAUN SALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BONTOMARANNU - Rahmawati Walahe; Fatma Jama; Sunarti; Mardiah (Jurnal Kesehatan, 2025)
Hypertension is one of the health problems whose prevalence continues to increase from year to year. This condition can cause serious complications if not controlled, so proper management efforts are needed. In addition to pharmacological therapy, there are non-pharmacological therapies that can be used as supportive alternatives. One of them is the use of bay leaf decoction which is believed to have an effect on lowering blood pressure. This study aims to determine the application of bay leaf decoction to reduce blood pressure in hypertensive patients. This study uses a case study approach on Mrs. R, a patient with a history of hypertension for two years. The patient's initial blood pressure was recorded at 170/105 mmHg with the main complaints being headache, dizziness, and blurred vision. The intervention carried out was the regular administration of bay leaf decoction, accompanied by blood pressure monitoring, subjective symptom assessment, and education about a healthy lifestyle. The results showed a decrease in the patient's blood pressure from 170/105 mmHg to 150/90 mmHg after the intervention. In addition, subjective complaints in the form of headaches were reduced from a scale of 5/10 to 4/10, accompanied by a decrease in dizziness and anxiety. Health education also increases patient understanding of the importance of regular check-ups, low-salt dietary arrangements, and adherence in managing hypertension. In conclusion, bay leaf decoction has been shown to be effective as a complementary therapy in helping to lower blood pressure and reduce symptoms of hypertension. This therapy is natural, easy to reach, and can be used as an alternative to support hypertension management in the community.